2015
DOI: 10.2217/nnm.15.149
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Social Complexity in Nanomedicine

Abstract: In this paper, I will discuss from a 'Science and Technology Studies' perspective three different modes of caring about the social complexity in biomedical and nanomedical research. Nanomedical research unfolds a variety of issues that generate different concerns, questions, problems, requirements and interests that connect with different systems of action (in vitro, in vivo), different kinds (human, nonhuman) and different scales of action (nano, micro, macro). To adequately address the social complexity, I w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…We broadly concur with Michael Schillmeier's () extremely perceptive and apposite analysis that calls on social science scholars to explore the social cross‐scalar complexity of nanomedicine. Equally, his critique of ELSI's excessive reliance on a humanist ontology, privileging ‘human agency’ (Schillmeier : 61) at the expense of the agency of the ‘more‐than‐human’ (2015b: 56), is particularly urgent in the field of nanomedicine.…”
Section: Introductionsupporting
confidence: 75%
“…We broadly concur with Michael Schillmeier's () extremely perceptive and apposite analysis that calls on social science scholars to explore the social cross‐scalar complexity of nanomedicine. Equally, his critique of ELSI's excessive reliance on a humanist ontology, privileging ‘human agency’ (Schillmeier : 61) at the expense of the agency of the ‘more‐than‐human’ (2015b: 56), is particularly urgent in the field of nanomedicine.…”
Section: Introductionsupporting
confidence: 75%
“…Kraus recently discussed the issue of quality, reliability and reproducibility in an editorial of Molecular Endocrinology, also discussing such publications for the general public [9]. In the present issue, Schillmeier discusses the complexity presented to all actors, from scientists, medical practitioners, regulatory agencies to the general public [35].…”
Section: Complexity Variability and Reproducibility In Biological Sciementioning
confidence: 96%
“…Siegwart et al reported a particularly interesting work in this respect [47]. Various different block copolymers (35) were cross-linked using 96 different multifunctional amines to form cross-linked polymer nanoparticles for RNA delivery. This gave a quite significant library of different nanoparticles, from which structure property relationships were deduced.…”
Section: Reproducibility and High-throughput Screeningmentioning
confidence: 99%
“… 3. On hesitation as a source of public modes of caring about science, technology and medicine, see Schillmeier (2015). …”
mentioning
confidence: 99%